THE CORRELATION BETWEEN SOCIOECONOMIC STATUS AND STUNTING IN TODDLERS AGED 2-4 YEARS(IN LERAN VILLAGE, MANYAR DISTRICT, GRESIK REGENCY) - Eva Silviana Rahmawati; Nanik Nuraini (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Stunting is the final indicator of all the factors that affect the growth and development of children in the first 2 years which will then have a negative impact when they get older. The purpose of this study was to determine the Socio-Economic Relationship with Stunting Incidence in Toddlers Age 2-4 Years in Leran Village, Manyar District, Gresik Regency. Method: Correlational  analytic  research  method, Case  Control  time  approach.  The population of all mothers and children under five aged 2-4 years, a large sample of 34 respondents using simple random sampling. The independent variable is socio-economic, the dependent variable is the incidence of stunting. Questionnaire data collection instrument and z-score value. Research analysis using Spearman test. Result: The results of the analysis using SPSS 16.0 for windows, obtained spearman (rs) = -0.360 and the value of Sig. 2 tailed (p) = 0.036 then p <0.05 H1 is accepted meaning that there is a socio-economic relationship with the incidence of stunting with p value (0.000). Conclusion: The results of this study are suggested to be a reference for respondents, health institutions, the community and further researchers in increasing knowledge about stunting.